2019
DOI: 10.1523/jneurosci.3094-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Myelinating Glia-Specific Deletion of Fbxo7 in Mice Triggers Axonal Degeneration in the Central Nervous System Together with Peripheral Neuropathy

Abstract: Myelination of axons facilitates the rapid propagation of electrical signals and the long-term integrity of axons. The ubiquitinproteasome system is essential for proper protein homeostasis, which is particularly crucial for interactions of postmitotic cells. In our study, we examined how the E3 ubiquitin ligase FBXO7-SCF (SKP1, Cul1, F-box protein) expressed in myelinating cells affects the axon-myelin unit. Deletion of Fbxo7 in oligodendrocytes and Schwann cells in mice using the Cnp1-Cre driver line led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Moreover, various studies have shown that persistent demyelination may result in axonal damage and neuron degeneration [7,8]. Indeed, therapeutical approaches promoting timely recovery of damaged myelin sheath is an urgent medical need for many neurological disorders, but to the best of our knowledge, progression has been limited.…”
mentioning
confidence: 99%
“…Moreover, various studies have shown that persistent demyelination may result in axonal damage and neuron degeneration [7,8]. Indeed, therapeutical approaches promoting timely recovery of damaged myelin sheath is an urgent medical need for many neurological disorders, but to the best of our knowledge, progression has been limited.…”
mentioning
confidence: 99%
“…Our data in Cnp-Mek1DD mice revealed significant improvement in EAE clinical score compared to controls, yet data using tamoxifen-inducible Plp-Mek1DD or Pdgfrα-Mek1DD mice did not support the conclusion that MEK1DD expression in the OL lineage provides a protective or reparative functional benefit. These data were surprising, given that Cnp-Cre has previously been reported to cause recombination specifically in the OL lineage in the CNS (Nishizawa et al., 1985; Trapp et al., 1988; Lappe-Siefke et al., 2003; Madsen et al., 2016; Mei et al., 2016; Joseph et al., 2019; Y. Yue et al., 2019).…”
Section: Resultsmentioning
confidence: 93%
“…The beam was connected to a darkened box of 13 x 22 cm, which had an entrance hole of 5 x 6 cm (Fig. 2) [14]. Footprints test.…”
Section: Obtaining Of Mmscs From Adipose Tissuementioning
confidence: 99%